Ni animal de compagnie, ni animal de travail : proximité et mise à l’écart du qimmiq (chien) dans les familles inuites de l’Arctique central canadien avant la sédentarisation - Lévesque, Francis (Centre Urbanisation Culture Société (UCS) de l'INRS, 2019)
Research Framework : This paper deals with the integration of qimmiq (dog) in Inuit families from the central Canadian Arctic before they moved to settlements in the mid-20th century. Objectives : Its first objective is to describe how the qimmiit were integrated into those Inuit families as well as the strategies they adopted to keep them away. It then tries to make sense of the apparent contradiction between its importance and the harsh treatments it could receive at times. Methodology : The paper leans on fifteen years of research about Inuit dogs in primary and secondary sources, on dozens of Inuit testimonies published in various books and on three periods of fieldwork in Iqaluit, Nunavut in 2004, 2016, and 2017. Results : It proposes a description of the traditional Inuit family as well as a description of how Inuit and their qimmiit interacted before the creation of settlements (economic importance, place in society, how they were treated, etc.). It will also describe the strategies used by Inuit to keep qimmiit away and distinct from humans. This paper also identifies a series of Inuit behaviour Westerners found either negligent or inhumane toward their dogs and thus contradictory with its importance. Conclusions : The paper shows that qimmiit are neither dogs nor working animals but occupy their own peculiar space. Despite first impressions, there is no contradiction between how harshly dogs were treated and their importance for Inuit. Contributions : This paper answers a gap in current literature. Whereas most publications deal with the qimmiq’s physical characteristics or with the dog slaughter that took place in the mid-20th century, few deals with the integration of dogs in Inuit families and with the apparent contradiction between their importance and the way they were treated. Cadre de la recherche : Cet article porte sur l’intégration du qimmiq (chien) dans les familles inuites de l’Arctique central canadien avant que celles-ci ne se sédentarisent au milieu du XXe siècle. Objectifs : Le présent ...